Application of evidence-based nursing combined with individualized health education intervention for patients undergoing gynecological surgery (循证护理联合个性化健康教育干预在妇科手术患者中的应用) - FAN Ying (范莹); ZHANG Hong (张宏); LIU Li (刘莉); ZHEN Qiao (郑巧); GAO Huiyun (高灰云); CHEN Cheng (陈程) (中西医结合护理)
Objective To investigate the effect of evidence-based nursing combined with individualized health education intervention on knowledge about deep vein thrombosis (DVT), self-management ability and discharge readiness of patients with gynecological surgery. Methods A total of 160 patients who underwent gynecological surgery in the hospital from January 2021 to December 2021 were selected as the research subjects. According to different health education methods, they were divided into control group and observation group, 80 cases in each group. The control group received routine health education, and the observation group received evidence-based nursing combined with personalized health education. The self-management ability ［self-care ability measurement scale (ESCA)］, DVT related knowledge (self-made DVT-related knowledge questionnaire), incidence of DVT and discharge readiness level ［Discharge Readiness Assessment Scale (RHDS)］ were compared between the two groups. Results After intervention, the total score and dimensional scores of ESCA in the two groups were increased (P<0. 01), and scores in the observation group were higher than those in the control group(P<0. 01). The total score and dimensional scores of DVT related knowledge questionnaire in the two groups were increased (P<0. 01), and scores in the observation group were higher than those in the control group(P<0. 01). Only 4 cases of DVT were reported in the control group. The total score of RHDS in the observation group (162. 28±10. 37) was significantly higher than that in the control group (134. 59±7. 69), with a significant difference (P<0. 01). Conclusion The implementation of evidence-based nursing combined with individualized health education intervention can improve the self-management ability and DVT-related prevention knowledge of patients undergoing gynecological surgery, and improve the discharge readiness of patients. (目的 探讨循证护理联合个性化健康教育干预对妇科手术患者深静脉血栓形成(DVT)相关知识、自我管理能力及出院准备度的影响。方法 选取2021年1月—12月医院妇科收治160例手术患者为研究对象。根据健康教育方式的不同分为对照组和观察组, 各80例。对照组实施常规健康教育, 观察组实施循证护理结合个性化健康教育。采用自我护理能力测定量表(ESCA)评估患者自我管理能力, 采用自制问卷调查患者DVT相关知识水平并统计DVT发生率, 采用出院准备度评估量表(RHDS)评估患者出院准备度水平。结果 干预后, 两组ESCA各分量表评分及总分均升高(P＜0. 01), 且观察组ESCA量表评分改善优于对照组(P＜0. 01)。两组DVT相关知识调查问卷各分量表及总分均升高(P＜0. 05), 且观察组评分高于对照组(P＜0. 05)。对照组有4(5. 00%)例患者发生DVT。观察组RHDS量表总分为(162. 28±10. 37)分, 高于对照组的(134. 59±7. 69)分(P＜0. 05)。结论 循证护理结合个性化健康教育干预能提高妇科手术患者自我管理能力及DVT相关预防知识, 提高患者的出院准备度水平。)